Validation and Application of the Positive Play Scale Adapted for Chinese Gamblers: Its Relation to Disordered Gambling and Gambling Attitudes - Tong, Kwok Kit; Chen, Juliet Honglei; Wu, Anise M. S. (Frontiers in Psychology, 2020)
The Positive Play Scale (PPS) was designed to track the effectiveness of responsible gambling (RG) policy, with a focus on positive changes in beliefs and behaviors instead of the absence of problem gambling symptoms. The current study aimed to (1) validate the Positive Play Scale Adapted for Chinese gamblers (PPS-AC) using a probability Chinese community sample in Macao, (2) explore the relationships between the PPS-AC and symptoms of gambling disorder (GD), and (3) evaluate the associations of gambling attitudes with the PPS-AC. Through a two-step random sampling procedure, we interviewed 1,002 locally dwelling Macao Chinese adults (44.3% males; Mage = 44.28 years, SDage = 17.35 years) by phone, in which 237 were past-year gamblers (49.8% males; Mage = 40.76 years, SDage = 15.78 years). Results showed that a two-dimension structure fitted the data well for both the positive play behaviors scale and the positive play beliefs scale of the PPS-AC among past-year gamblers. In addition to findings of satisfactory internal consistency, the convergent validity of the PPS-AC was supported by its significant association with RG self-efficacy. All four PPS-AC constructs were negatively correlated with GD symptoms, whereas two behavior constructs of the PPS-AC significantly explained the variance of GD symptoms with negative valences. All gambling attitude dimensions were associated with at least one PPS-AC construct. The current study was the first to adapt the PPS on a probability Chinese community sample and extended its applicability. The findings support the PPS-AC as a reliable and valid tool for assessing positive play, which was negatively associated with symptoms of disordered gambling. Further, the significant associations between gambling attitudes and the PPS-AC provide insights for RG policies.